IMPROVEMENT OF VIGOR AND EARLY GROWTH OF TWO COMPOSITE MAIZE VARIETIES THROUGH SEED PRIMING TREATMENT - Muhammad Kadir; Muhammad Dzulkifly Ashan; Syamsia Syamsia (ITScience (Information Technology and Science), 2023)
One factor affecting productivity is the quality of seeds with good initial seed vigor indicators, but less than optimum growing environment conditions also affect seeds' growth and initial Vigor. One of the technologies that can improve it is giving priming treatment to the seeds before planting. This study aims to see the effect of priming treatment to improve the quality of Vigor and early growth of 2 composite corn varieties, namely Sukmaraga and Bisma. The research was carried out in the laboratory and the Green House, with the experimental method using a Completely Randomized Design (CRD) with each seed of the two varieties treated with Hydropriming (soaking seeds before planting) using Ion-Free Water (IFW) for 30 minutes, 12 hours, and 24 hours plus a control treatment without Priming, and priming using PGR made from sodium orthonitrifenol 0.2%, sodium 2,4-dinitrophenol 0.05% both as controls. So there are a total of 10 treatments. The results showed that priming treatment greatly influenced the germination, where all Hydropriming treatments gave average germination above 88%, significantly different from seeds without priming below 82%. The hypocotyl length ratio of Sukmaraga and Bisma corn seeds was also different from the treatment without priming. Seeds with hydropriming for 12 hours showed the best field growth percentage, reaching 96.7% (Sukmaraga variety) and 96.98% (Bisma variety).